ANALISIS KEMAMPUAN MENYIMAK CERITA RAKYAT PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN INPRES TOLOTANGGA - Sri Yuliyanti; Desy Ningsih Komalasari; Rizalul Fiqry (Universitas Batanghari, 2026)
This study is a qualitative research employing a descriptive research design. It aims to determine the listening skills of fourth-grade students at SDN Inpres Tolotangga and to identify the solutions implemented by teachers to overcome the related problems. The results of the study indicate that the students’ ability to listen to folklore in the Indonesian Language subject varies. Based on the findings from 14 students, 5 students were categorized as good, 3 students as fairly good, 3 students as very good, and 3 students as poor. The inhibiting factors in listening to stories include the use of vocabulary that is not appropriate to the students’ level of understanding, distractions that affect concentration, and the low interest of students in reading and listening. As a result, students experience difficulties in listening and demonstrate a lack of concentration when listening to the stories being read.Efforts to improve students’ listening skills in folklore within the Indonesian Language subject for fourth-grade students include creating a pleasant and interactive atmosphere during listening sessions, using various techniques such as storytelling with engaging intonation and a clear voice, asking questions to assess students’ level of understanding, and providing constructive feedback to enhance students’ interest and comprehension